Exercise and the Liver: Implications for Therapy in Fatty Liver Disorders - Johnson, Nathan A.; Keating, Shelley E.; George, Jacob (Seminars in Liver Disease, 2012)
The increasing recognition that fatty liver plays a direct role in the pathogenesis of cardiovascular and metabolic disease has resulted in significant research enquiry into the efficacy of lifestyle therapy in modulating liver fat. Recently, this has extended to the specific investigation of a possible independent benefit of physical activity/exercise in nonalcoholic fatty liver disease (NAFLD). In this article we review the effect of acute and regular exercise (training) on metabolism, including liver glucose and lipid metabolism, and the available human trials that have compared the benefit of regular exercise versus a nonexercise control on liver fat. The limited human research suggests that exercise can reduce liver fat and that this benefit may be mediated, in part, by a reduction in hepatic lipogenesis. The relative importance of extrahepatic adaptations and acute versus regular exercise in explaining this benefit are discussed. From a clinical perspective, the revelation of a benefit of exercise per se offers a novel approach for liver fat reduction, and highlights the importance of incorporating fitness assessment and prescription in the management of patients with fatty liver disorders. Implementation of exercise therapy in a clinical setting is arguably the biggest challenge because evidence shows that mere provision of information about the benefits of exercise and/or exercise prescription to the patient does not translate to positive outcomes. Rather, the focus should be on implementing strategies to promote behavior change including regular contact and assessment with a health care professional, self-monitoring, and personalization of goals that focus on changing physical activity behavior.
Keywords: NAFLD; physical activity; aerobic; resistance training; obesity; weight loss